2024
DOI: 10.1037/xlm0001326
|View full text |Cite
|
Sign up to set email alerts
|

Action consequences guide the use of visual working memory.

Andre Sahakian,
Surya Gayet,
Chris L. E. Paffen
et al.

Abstract: Visual working memory (VWM) is a store for temporary maintenance of visual information. It is often disregarded, though, that information is typically stored to enable actions. Therefore, the context of these actions is of great importance for how VWM is used. Here, we questioned whether the severity of the consequence of an action might affect how well information is memorized, and how cautiously it is utilized. We employed an (online) copying task, in which participants reproduced an example display comprise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Therefore, VWM can be regarded as being part of a dynamic system that constantly weighs the costs of maintaining a (high) memory load against the costs of external sampling. Indeed, consistent with the example of a jigsaw puzzle, several studies have found participants to minimally utilize VWM in many circumstances where information could be retrieved just-in-time from the environment instead (Ballard et al, 1995;Böing et al, 2023;Draschkow et al, 2021;Droll & Hayhoe, 2007;Gajewski & Henderson, 2005;Gray et al, 2006;Hayhoe et al, 2003;Inamdar & Pomplun, 2003;Melnik et al, 2018;Risko & Dunn, 2015;Risko & Gilbert, 2016;Sahakian et al, 2023Sahakian et al, , 2024Somai et al, 2020;Triesch et al, 2003). In this just-in-time approach, external information is only fixated and encoded into memory if and when it is needed for the task at hand, instead of being processed (and memorized) in advance (Droll & Hayhoe, 2007;Hayhoe et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, VWM can be regarded as being part of a dynamic system that constantly weighs the costs of maintaining a (high) memory load against the costs of external sampling. Indeed, consistent with the example of a jigsaw puzzle, several studies have found participants to minimally utilize VWM in many circumstances where information could be retrieved just-in-time from the environment instead (Ballard et al, 1995;Böing et al, 2023;Draschkow et al, 2021;Droll & Hayhoe, 2007;Gajewski & Henderson, 2005;Gray et al, 2006;Hayhoe et al, 2003;Inamdar & Pomplun, 2003;Melnik et al, 2018;Risko & Dunn, 2015;Risko & Gilbert, 2016;Sahakian et al, 2023Sahakian et al, , 2024Somai et al, 2020;Triesch et al, 2003). In this just-in-time approach, external information is only fixated and encoded into memory if and when it is needed for the task at hand, instead of being processed (and memorized) in advance (Droll & Hayhoe, 2007;Hayhoe et al, 2003).…”
Section: Introductionmentioning
confidence: 88%